The Effect of Effleurage Massage on Reducing the Intensity of Pain in the First Stage of Active Labor - Octavia, Rina; Lustiani, Ika; Fathiyati, Fathiyati; Safitri, Reni; Oktaviana, Agriyaningsih (Jurnal Biologi Tropis, 2024)
Childbirth is a process of expelling the results of fertilization through a flask from inside the uterus out of the uterus through the vagina spontaneously. Pain is an experience of feeling uncomfortable and unpleasant from a person's sensory and emotional side. The purpose of this study was to determine the effect of Mensage Effinage on reducing the intensity of labor pain in the first active phase. This study used a one-group pre-test post-test design experiment with a sample of 34 respondents. Data was collected using a Verbal Descriptor Scale (VDS) monitoring observation sheet. Data analysis using the normality test on the Wilcoxon Sign Ronk Anamis pararsenic test because the data is not normally distributed or has Wilcoxon status. The results of the study showed that the intensity of pain in the first stage of labor in the active phase can be reduced through effluent massage therapy. This is evidenced by the results of data analysis where p = 0.000 <0.05 so that the Ho result is rejected, H1 is accepted. Effluent Massage Therapy can be used as an alternative that needs to be applied to reduce pregnancy pain in mothers giving birth in the first phase of pregnancy. The conclusion is that massage effluent can reduce the intensity of pain in pregnant women in phase 1.